GAMBARAN HISTOLOGIS HEPAR MENCIT (Mus musculus L.) STRAIN DDW SETELAH PEMBERIAN EKSTRAK N-HEKSAN BUAH ANDALIMAN (Zanthoxylum acanthopodium DC.) SELAMA MASA PRA IMPLANTASI DAN PASCA IMPLANTASI - Eka Prasetiawan; Emita Sabri; Syafruddin Ilyas (Saintia Biologi, 2012)
Liver histological features of DDW mice (Mus musculus L.) treated with n-hexane extract of Andaliman (Zanthoxylum acanthopodium DC.) fruit during pre- and post-implantation has been studied in Laboratory of Animal Structure, Department of Biology, Faculty of Mathematics and Natural Science, University of Sumatera Utara, Medan. Experiment used completely randomized design (CRD) consisted of 2 periods of treatment: pre-implantation (day 0-3; group A) and post-implantation (day 6-14; group B). For each group, mice were treated daily by oral gavage with 0, 1, 2, 4, or 6 % of andaliman extract in 0.3 ml of 1% CMC. The result showed, liver in treatment groups was pale and showed mottled surface texture. Hepatocyte damage in post-implantation group was higher than in pre implantation group (p> 0.05). We concluded that n-hexane extract of andaliman fruit appears to negatively affect liver histology of mice. Keywords: liver histology, andaliman (Zanthoxylum acanthopodium DC.), post implantation, pre implantation